Indonesian EFL Students’ Motivation in Online English Learning in the Emergency Remote Teaching Context - Miftahul Janah; Bambang Yudi Cahyono (International Journal of Language Education, 2022)
Due to the massive spread of the coronavirus disease (COVID-19) in Indonesia, teachers are demanded to make immediate plans for online teaching. Online teaching aimed to maintain the teaching quality as well as to get the students to feel more motivated in learning. Of the various studies on motivation and its role in students’ English learning, research that specifically focused on how students promote motivation to learn English remotely is still limited. This study, therefore, investigated the students’ motivation in online English learning and found out factors that affect their motivation. To get the data, an online survey questionnaire was created and distributed by using Google Forms. The results show that students have a medium level of positive motivation in online English learning. Some factors that strongly affect the level of motivation includes learning attitudes (having a strong desire to learn English), self-confidence (the capability to join the online English learning well) and influence of other people (family members and lecturers).